2018
DOI: 10.1200/jco.18.01219
|View full text |Cite
|
Sign up to set email alerts
|

Longer Follow-Up Confirms Relapse-Free Survival Benefit With Adjuvant Dabrafenib Plus Trametinib in Patients With Resected BRAF V600–Mutant Stage III Melanoma

Abstract: PurposeDabrafenib plus trametinib improved relapse-free survival (RFS) versus placebo (hazard ratio [HR], 0.47; P < .001) in patients with resected BRAF V600–mutant stage III melanoma (BRF115532; COMBI-AD; ClinicalTrials.gov identifier: NCT01682083). We present an updated RFS analysis on the basis of extended study follow-up and a cure-rate model analysis to estimate the fraction of patients expected to remain relapse free long term.MethodsIn this phase III trial, patients with resected BRAF V600–mutant stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
151
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 217 publications
(161 citation statements)
references
References 21 publications
6
151
0
4
Order By: Relevance
“…This could be explained by the likely underestimation of stage IIIC disease in our study, resulting from a lack of information about the number of involved lymph nodes in a considerable number of patients. Currently, the effective novel therapies are introduced in the adjuvant setting as routine care . It is therefore likely that the survival of patients with stage III disease will significantly improve in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the likely underestimation of stage IIIC disease in our study, resulting from a lack of information about the number of involved lymph nodes in a considerable number of patients. Currently, the effective novel therapies are introduced in the adjuvant setting as routine care . It is therefore likely that the survival of patients with stage III disease will significantly improve in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Some preclinical models suggested that neoadjuvant therapy with clinically detectable volumes of disease would be required to induce long‐term disease control . These preclinical concerns surrounding an overt tumor microenvironment being a requirement for anti‐PD1 activity have been settled in melanoma, however, with the reporting of multiple international adjuvant therapy clinical trials of completely resected stage IIIB and IIIC (AJCCv7) and stage IV disease (Table ) . In the CheckMate 238 study (Efficacy Study of Nivolumab Compared to Ipilimumab in Prevention of Recurrence of Melanoma After Complete Resection of Stage IIIB/IIIC or Stage IV Melanoma) of stage III and IV melanoma (stages IIIB and IIIC, resected stage IV; AJCCv7), nivolumab demonstrated superiority to ipilimumab in terms of both relapse‐free survival (RFS) and toxicity profile.…”
Section: Role Of Anti‐pd1 Therapy In Melanomamentioning
confidence: 99%
“…The combination of dabrafenib and trametinib has also been evaluated as adjuvant therapy in the COMBI‐AD trial (A Phase III Randomized Double Blind Study of Dabrafenib [GSK2118436] in Combination With Trametinib (GSK1120212) Versus Two Placebos in the Adjuvant Treatment of High‐Risk BRAF V600 Mutation‐Positive Melanoma After Surgical Resection), treating patients with resected stage III disease (Table ). Long‐term RFS data have now been reported and, at a median follow‐up of 44 months (dabrafenib plus trametinib) and 42 months (placebo), the 4‐year RFS rates were 54% (95% CI, 49%‐59%) in the dabrafenib plus trametinib arm and 38% (95% CI, 34%‐44%) in the placebo arm, respectively (hazard ratio [HR], 0.49; 95% CI, 0.40‐0.59). The estimated cure rate was 54% (95% CI, 49%‐59%) in the dabrafenib plus trametinib arm compared with 37% (95% CI, 32%‐42%) in the placebo arm.…”
Section: The Role Of Targeted Therapy In Braf‐mutant Melanomamentioning
confidence: 99%
See 2 more Smart Citations